Penataan Kelembagaan dan Sumberdaya Manusia Pengelola Wisata Volcano Merapi - Pribadi, Ulung; Zaenuri, Muchamad (Universitas Muhammadiyah Yogyakarta, 2017)
Tourism activities are very affected by the disaster, not exception in the Special Region of Yogyakarta, the perpetra-tors of tourism is devastated by the eruption of Mount Merapi. When Mount Merapi erupts, the number of tourist visits in Yogyakarta drops dramatically to 80% (BPS DIY, 2012). Similarly, it happened in Sleman regency, one of the regencies located in the north of the Special Province of Yogyakarta which is an area with many interesting objects and tourist attraction (ODTW). The impact of this eruption is hitting both the government and Sleman communities especially those directly affected by the impact of the disaster. Although now the eruption is over but still leaves the problem, whether it is a socio-economic problem in the vicinity of Mount Merapi and tourism itself. After conducive situation, local government also can not do the maximum. The availability of human resources (HR) to manage these newly emerging disasters is also not available. It also gives the impression that between the ranks of local government and village government there is no coordination. After the issuance of a letter from the Sleman Regent then the Umbulharjo Village Government was given the authority to manage the Merapi volcano tour area. Through the village regulations finally formed the team of volcano area tour manager of Merapi. The performance of this team after working for 3 (three) years is still not optimal, after through the pre-survey and direct observation to the location it can be seen that the main problem now related to the institutional and human resources supporters. In connection with the above, it is necessary to have community service activities to assist the institutional arrangement and improvement of human resources competence of the manager. Activities that have been carried out include the fulfillment of minimal requirements for secretarial office, nameplate and brochures for the purpose of the existence of organization and tourism services, the preparation of strategic plan documents (renstra) that can be used as a reference for the preparation of work programs, organizational structure and job descriptions that can be used all members to work directed and appropriate field of duty, and websites that can be used for service and tourism promotion. After this community service program ends, most of Merapi volcano tour managers are able to manage the organization and mobilize resources effectively. Keywords: institutional, human resources, volcano tour of Merapi.